Kelayakan Ekonomi dan Strategi Pengembangan Usaha Pertanian Perkotaan KWT Anggrek di Kota Makassar - Nurhanis Abdullah; Muhammad Rakib; Muhammad Hasan; Nurdiana Nurdiana; Tuti Supatminingsih (Ideas Publishing, 2022)
Urban agriculture is part of agricultural activities that are specifically carried out in urban areas and not a few of these urban activities are used as business or business land by urban communities where this gives rise to many businesses established by urban farming actors, so it is necessary to analyze efforts so that the business is feasible to run and can provide benefits for the urban farming actors. This study aims to see the economic feasibility of urban farming, namely the Women s Orchid Farmer s Group in terms of production, marketing and financial aspects and to formulate a good strategy used by the Orchid Women Farmer Group to develop its business. This research was conducted at the Orchid Women Farmer Group in Lorong 4 Bara-Barayya Village, Makassar District, Makassar City by analyzing every aspect with the interview, observation and documentation methods and using Net Present Value and Payback Period analysis to calculate economic feasibility in the financial aspect and using the Forum Group. Discussion in formulating what are the weaknesses, strengths, opportunities and threats of the Orchid Women Farmer Group. The results obtained are that in the production aspect it can be said to be feasible, in the marketing aspect it can be said to be feasible and in the financial aspect, especially in the calculation of the Net Present Value it produces -8.350.133 and is said to be not feasible in accordance with the provisions of the NPV and the Payback Period calculation shows decent results. of 1.94 means that it takes as much as 1 year, 9 months and 4 days to return the investment capital that has been issued and is said to be feasible to continue. In addition, one of the formulations for a business development strategy was produced, one of which was creating innovative products from agricultural plant products.